Aplikasi Particle Swarm Optimization Pada Pemasangan Kapasitor Bank Pada Jaringan Distribusi - Mudjiono; Priya Surya Harijanto; Imron Ridzki (Politeknik Negeri Malang, 2021)
The length of conductor paths in distribution networks often leads to voltage drop issues and significant network losses. Placing capacitor banks in the distribution network is the primary solution to address these problems. However, optimizing the installation to achieve a significant impact on the voltage level in the network requires complex calculations, especially for very long lines such as in the 20 kV medium voltage network. This paper will use a 20 kV primary distribution system with 10 buses and 9 lines. Based on operational conditions, there are several issues that need to be addressed, and their solutions will be sought through heuristic methods.